Greece : Report on the Observance of Standards and Codes-Fiscal Transparency Module-Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper presents an update to the Report on the Observance of Standards and Codes (ROSC)-Fiscal Transparency Module for Greece. As noted in previous updates of the fiscal ROSC, much progress has been made in Greece since joining the European Union in separating government from nongovernment functions, and more tightly delineating the boundaries between the government and the rest of the public sector. For this purpose, a consistent legal framework has been developed. However, there are a few areas where roles and responsibilities could be more clearly defined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet